Indian foreign policy in transition relations with South Asia - Mazumdar, Arijit (Routledge contemporary South Asia series, 2015)
India's relation with other South Asian countries has been impacted by recent developments in the post-Cold War period. These include India's economic rise, the recent democratic transitions in many South Asian countries and greater US engagement in the region following 9/11. This book is an effort to address these issues and examine their role in India's interactions with its neighbours. Indian Foreign Policy in Transition provides a comprehensive overview of India's relations with the South Asian countries of Pakistan, Afghanistan, Bangladesh, Sri Lanka and Nepal, Bhutan and the Maldives. As well as looking at India's past and present foreign policy, the book analyses recent political changes and developments. It identifies the broad tenets of India's policy towards the other countries of South Asia, and the domestic factors that impact India's policy in the region. It looks at India's historical patterns of interactions with its neighbours, and describes recent developments in these South Asian countries and their perceptions of India. By providing specific examples of the major disputes and conflicts between India and its neighbours, the book explores the challenges inherent in promoting peace and cooperation, and goes on to highlight the growing US influence in South Asia. Providing an in-depth discussion on the opportunities and challenges facing India in the South Asia region, the book is an important contribution to Indian and South Asian Politics, Foreign Policy, and International Relations.